2014
DOI: 10.1051/0004-6361/201323139
|View full text |Cite
|
Sign up to set email alerts
|

HST observations of the limb polarization of Titan

Abstract: Context. Titan is an excellent test case for detailed studies of the scattering polarization from thick hazy atmospheres. Accurate scattering and polarization parameters have been provided by the in situ measurements of the Cassini-Huygens landing probe. For Earth-bound observations Titan can only be observed at a backscattering situation, where the disk-integrated polarization is close to zero. However, with resolved imaging polarimetry a second order polarization signal along the entire limb of Titan can be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…With the highly successful New Horizons flyby of Pluto, we now have a rich atmospheric data set for another hazy N 2 /CH 4 /CO atmosphere; comparative planetology investigations in the coming years should improve our understanding of both atmospheres. Additionally, since a large number of exoplanets appear to have an aerosol absorber in their atmospheres [see, e.g., Kreidberg et al, 2014;Knutson et al, 2014aKnutson et al, , 2014b, which may be photochemically produced [Marley et al, 2013], there is increasing interest in using Titan as an exoplanet analogue [Lunine, 2010;Bazzon et al, 2014;Robinson et al, 2014].…”
Section: Outstanding Questions and The Futurementioning
confidence: 99%
“…With the highly successful New Horizons flyby of Pluto, we now have a rich atmospheric data set for another hazy N 2 /CH 4 /CO atmosphere; comparative planetology investigations in the coming years should improve our understanding of both atmospheres. Additionally, since a large number of exoplanets appear to have an aerosol absorber in their atmospheres [see, e.g., Kreidberg et al, 2014;Knutson et al, 2014aKnutson et al, , 2014b, which may be photochemically produced [Marley et al, 2013], there is increasing interest in using Titan as an exoplanet analogue [Lunine, 2010;Bazzon et al, 2014;Robinson et al, 2014].…”
Section: Outstanding Questions and The Futurementioning
confidence: 99%
“…Observations of individual objects have shown that for Rayleigh scattering atmospheres like Uranus and Neptune (Schmid et al 2006b) the fractional polarization can be substantially higher than this value (p(90 • ) > 20 %). For mostly haze scattering atmospheres as found on Titan (Tomasko & Smith 1982;Bazzon et al 2014) or in the polar regions of Jupiter (Smith & Tomasko 1984;Schmid et al 2011;McLean et al 2017) the fractional polarization can even reach values up to p(90 • ) ≈ 50 %. On the other hand, the Mie scattering process in the clouds that dominate the atmospheres of Venus, Saturn or the equatorial regions of Jupiter produces a lower polarization in the visual wavelengths < 10 % (Smith & Tomasko 1984;Hansen & Hovenier 1974).…”
Section: The Polarization Of the Reflected Light From Planetsmentioning
confidence: 95%
“…The q(θ pp ) = q(θ, 0 • : 180 • ) curve shows a weakly negative section around the back-scattering directions θ pp = 50 • −80 • . This is a well-known higher order scattering effect (e.g., van de Hulst 1980), which for dust (or haze) scattering in Jupiter and Titan leads to strong "negative" limb polarization effects (Schmid et al 2011;McLean et al 2017;Bazzon et al 2014).…”
Section: Calculations For a Plane Parallel Surfacementioning
confidence: 96%